Wealth shocks, credit-supply shocks, and asset allocation: Evidence from household and firm portfolios - Thomas Kick; Benedikt Ruprecht; Enrico Onali; Klaus Schaeck (Deutsche Bundesbank, 2014)
We use a unique dataset with bank clients' security holdings for all German banks to examine how macroeconomic shocks affect asset allocation preferences of households and non-financial firms. Our analysis focuses on two alternative mechanisms which can influence portfolio choice: wealth shocks, which are represented by the sovereign debt crisis in the Eurozone, and credit-supply shocks which arise from reductions in borrowing abilities during bank distress. We document heterogeneous responses to these two types of shocks. While households with large holdings of securities from stressed Eurozone countries (Greece, Ireland, Italy, Portugal, and Spain) decrease the degree of concentration in their security portfolio as a result of the Eurozone crisis, non-financial firms with similar levels of holdings from stressed Eurozone countries do not. Credit-supply shocks at the bank level (caused by bank distress) result in lower concentration, for both households and non-financial corporations. We also show that only shocks to corporate credit bear ramifications on bank clients' portfolio concentration, while shocks in retail credit are inconsequential. Our results are robust to falsification tests, propensity score matching techniques, and instrumental variables estimation.
Keywords: D12; D13; G11; G21; 330; asset allocation; sovereign debt crisis; credit-supply shocks; bank distress